Concrete walls weakened by openings as compression members: A review. (15th April 2015) - Popescu, Cosmin; Sas, Gabriel; Blanksvärd, Thomas; Täljsten, Björn
Highlights: A review of current design models on axially loaded concrete walls. An up-to-date database with experimental tests on concrete walls with and without openings. Statistical assessment of existing design models on axially loaded concrete walls. Techniques for strengthening concrete walls with openings using fiber-reinforced polymers. Research gaps have been highlighted. Abstract: The purpose of this paper is to review the advances that have been made in the design of monolithic and precast reinforced concrete walls, both with and without openings, subject to eccentrically applied axial loads. Using the results of previous experimental studies, a database was assembled to enable statistical assessment of the reliability of existing design models. Several design aspects are highlighted, including the size and position of openings, and the roles of boundary conditions and geometric characteristics. In addition, the performance of fiber-reinforced polymers in strengthening wall openings is discussed. Overall it is found that design codes provide more conservative results than alternative design models that have been proposed in recent studies. Research into the strengthening of walls with openings is still in its early stages, and further studies in this area are needed. The paper therefore concludes by highlighting some areas where new investigations could provide important insights into the structural behaviour of strengthened elements.